2021
DOI: 10.1080/02699052.2021.1972149
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe traumatic brain injury in regions with limited resources

Abstract: Importance: Severe traumatic brain injury (sTBI) is a critical health problem in regions of limited resources (RLRs). Younger populations are among the most impacted. The objective of this review is to analyze recent consensus-based algorithms, protocols and guidelines proposed for the care of patients with TBI in RLRs. Observations: The principal mechanisms for sTBI in RLRs are road traffic injuries (RTIs) and violence. Limitations of care include suboptimal or non-existent pre-hospital care, overburdened eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Precisely, we refer to patients admitted to an urban spoke hospital without neurosurgical capabilities in a high-income country with the availability of an intensive care unit (ICU), operating room (OR) and computed tomography (CT) scan. In the case of severe TBI with extra-cranial lesions or admitted to hospitals with limited resources, readers can refer to several published articles/guidelines for initial management [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Precisely, we refer to patients admitted to an urban spoke hospital without neurosurgical capabilities in a high-income country with the availability of an intensive care unit (ICU), operating room (OR) and computed tomography (CT) scan. In the case of severe TBI with extra-cranial lesions or admitted to hospitals with limited resources, readers can refer to several published articles/guidelines for initial management [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, in the LABIC survey mentioned above, only 14.6% of responders indicated that they monitored brain oxygenation; half of them used jugular bulb oxygen saturation, and only 2% among all responders used invasive brain tissue oxygenation monitoring [ 20 ]. Along these lines, the interesting question raised is, if possible, how one can mitigate the various SBI mechanisms via less invasive and less resource-demanding approaches [ 25 ].…”
Section: Btf Guidelinesmentioning
confidence: 99%
“…A recent review summarizes the evidence for severe TBI management in LMICs [73 ▪▪ ]. CREVICE protocol, based on an expert consensus approach, includes three levels of interventions and recommendations for monitoring, general measures, goals for cerebral perfusion and oxygenation treatment and for escalation or tapering therapies [32 ▪▪ ].…”
Section: Recommendations From Low-income and Middle-income Countriesmentioning
confidence: 99%